Archives in a Wider World: The Culture and Politics of Archives - Tyacke, Sarah (Archivaria, 2001)
This is a reflective essay on some of the cultural, literary criticism, historical, and postmodern implications for records management and archiving, archives, and archivists from a point of view situated in the Unite d Kingdom. It is based on observing the changes, over the past ten years, in th e position of archives in various countries' perceptions. The author maintain s that archivists have the critical role of producing an archiving resolution of the tensions in soci ety at any one time between what should be kept and destroyed, and what should be open and closed-- bot h for the present and, more importantly, for future generations. Archivists need to make the manner of the archival resolution clear and understand the inherent bi ases in the processes necessary to achieve that resolution.